1995
DOI: 10.1093/oxfordjournals.humrep.a135770
|View full text |Cite
|
Sign up to set email alerts
|

Fetal loss in the first trimester after demonstration of cardiac activity: relation of cytogenetic and ultrasound findings

Abstract: A retrospective comparison of cytogenetic and ultrasound findings in first trimester spontaneous fetal loss after demonstration of cardiac activity was made. The crown-rump length (CRL) was measured twice for each fetus resulting in spontaneous abortion: (i) CRL was measured in the viable state while demonstrating cardiac activity, and the growth deviation was expressed as the measured/expected CRL ratio (M/E CRL ratio); (ii) in the same fetus, CRL was measured after confirmation of fetal death, and designated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
0
24
2
Order By: Relevance
“…A retrospective study of 102 early miscarriages could not find any significant difference in ultrasound landmarks between cases with euploidy and aneuploidy, but the incidence of aneuploidy was low and a high rate of maternal contamination in the cytogenetic analysis was suspected (89.6% 46,XX in euploid cases) (5). Likewise, in another retrospective comparison of cytogenetic results and ultrasound findings in 30 firsttrimester miscarriages with previous demonstration of heart activity, Bessho et al (10) found that measured/estimated ratio of CRL among fetuses that later miscarried was smaller than that of a normal control group. Presumably because of the small size of the study group, the difference between euploid and aneuploid samples was not statistically significant (10).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A retrospective study of 102 early miscarriages could not find any significant difference in ultrasound landmarks between cases with euploidy and aneuploidy, but the incidence of aneuploidy was low and a high rate of maternal contamination in the cytogenetic analysis was suspected (89.6% 46,XX in euploid cases) (5). Likewise, in another retrospective comparison of cytogenetic results and ultrasound findings in 30 firsttrimester miscarriages with previous demonstration of heart activity, Bessho et al (10) found that measured/estimated ratio of CRL among fetuses that later miscarried was smaller than that of a normal control group. Presumably because of the small size of the study group, the difference between euploid and aneuploid samples was not statistically significant (10).…”
Section: Discussionmentioning
confidence: 95%
“…In a small series of first-trimester miscarriages the ratio between measured and expected CRL was smaller in cases of miscarriage than in normal pregnancies, but the study did not discriminate between euploidy and aneuploidy (10). On the other hand, in a series of 137 miscarriages, Coulam et al (11) did not find a relation between ultrasound findings and karyotype.…”
mentioning
confidence: 75%
“…It is well known that the most common cause of first trimester loss is embryonic aneuploidy [1,3,7,14,15]. However, the benefit of performing a karyotype on the POC after miscarriage is debated.…”
Section: Discussionmentioning
confidence: 99%
“…When a miscarriage occurs, patients are often concerned not only with the cause of the miscarriage but also with the risk of recurrence. The majority (50-76%) of these losses is due to embryonic aneuploidy [1][2][3][4][5][6][7][8][9]. Although not uniformly shown in all studies, some authors have found that women who miscarry genetically normal embryos have higher recurrence rates than those who miscarry aneuploid embryos [4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although POC has traditionally been used to detect chromosomal abnormalities in pregnancy loss [13], this report clearly illustrates the limitations of POC. In con trast, TAP commonly yielded findings representing the fetus that were missed by POC.…”
Section: Discussionmentioning
confidence: 83%